Math, asked by vjindha, 3 months ago

find the value of (z) =6z - 3z square + 3 at ,z=2 , z=-2,z= 0
plz help me gauys

Answers

Answered by RiyaSethi17
0

Answer:

hey mate here is your answer...

Step-by-step explanation:

Given,

z=(2−3i)

z

2

−4z+13

=(2−3i)

2

−4(2−3i)+13

=−5−12i−8+12i+13

=−12i+12i−5−8+13

=0

4z

3

−3z

2

+2z+170

=4(2−3i)

3

−3(2−3i)

2

+2(2−3i)+170

=4(−46−9i)−3(−5−12i)+2(2−3i)+170=4(−46−9i)−3(−5−12i)+2(2−3i)+170

=−184−36i−3(−5−12i)+2(2−3i)+170

=−184−36i+15+36i+4−6i+170

=5−6i

Similar questions